Gut microbiome modulation via fecal microbiota transplant to augment immunotherapy in patients with melanoma or other cancers - McQuade, Jennifer L (Curr Oncol Rep, 2020)
PURPOSE OF REVIEW: We review emerging evidence regarding the impact of gut microbes on anti-tumor immunity, and ongoing efforts to translate this in clinical trials. RECENT FINDINGS: Pre-clinical models and human cohort studies support a role for gut microbes in modulating overall immunity and immunotherapy response, and numerous trials are now underway exploring strategies to modulate gut microbes to enhance responses to cancer therapy. This includes the use of fecal microbiota transplant (FMT), which is being used to treat patients with Clostridium difficile infection among other non-cancer indications. The use of FMT is now being extended to modulate gut microbes in patients being treated with cancer immunotherapy, with the goal of enhancing responses and/or to ameliorate toxicity. However significant complexities exist with such an approach, and will be discussed herein. SUMMARY: Data from ongoing studies of FMT in cancer will provide critical insights for optimization of this approach.